PENGARUH INTERAKSI PERSONAL, DESAIN, KUALITAS LINGKUNGAN FISIK DAN HASIL TERHADAP KEPUASAN DAN DAMPAKNYA TERHADAP KEPERCAYAAN NASABAH TABUNGAN PT. BANK KALBAR CABANG UTAMA PONTIANAK - B2042141016, Silverius Ficho Khoman (Universitas Tanjungpura, 2019)
The purpose of this study is to test and analyze the Effect of Quality Perception Services Consisting Of Variable Interaction Personal, Design, Quality Of The Physical Environment And The Result Of Influence Of Satisfaction And Its Impact On The Trust Customer Savings PT. Bank Kalbar Cabang Utama Pontianak. This form of research is causal with a quantitative approach. Data collection using primary data in the form of questionnaires and interviews and secondary data in the form of data sourced from customers of PT. Bank Kalbar Cabang Utama Pontianak. The sample uses purposive sampling. The sample in this research is 100 people. The results showed that the First Personal Interaction, Design, Environmental Quality and Results, satisfying the results of satisfaction with significant values of 0.003, 0.001, 0.000 and 0.001. Second Personal Interaction, Design, Environmental Quality, and Satisfactory Results from the calculation results with a significant value of 0,000, 0,021, 0,001, 0,000 and 0,017 for the customer confidence of PT. Bank Kalbar Cabang Utama Pontianak. Keywords : Organizational Climate, Organizational Commitment, Job Satisfaction, Organizational Citizenship Behavior and Performance